Serials Librarianship in Transition: Issues and Developments, 1st edition - Gellatly, Peter (Routledge, 2020)
This book, first published in 1986, contains the invaluable and enlightening perspectives of an international roster of experts on the state-of-the-art of serials librarianship and the indications for the future of the profession.